Growth, Gas Exchange, and Mineral Nutrients of Hydrangea Hybrids Irrigated with Saline Water - Youping Sun; Genhua Niu; Haijie Dou; Christina Perez; Lisa Alexander (HortScience, 2022)
Hydrangeas are popular landscape plants that are widely grown in many parts of the world. The objective of this study was to evaluate the salinity tolerance of three novel Dichroa ×hydrangea hybrids [Dichroa febrifuga ‘Yamaguchi Hardy’ × Hydrangea macrophylla ‘Hamburg’ (YH × Hamburg), Dichroa febrifuga ‘Yellow Wings’ ×Hydrangea macrophylla ‘Nigra’ (YW × Nigra), and Dichroa febrifuga ‘Yellow Wings’ ×Hydrangea macrophylla ‘Oakhill’ (YW × Oakhill)]. A 52-day greenhouse study was conducted by irrigating container-grown plants with nutrient solution at an electrical conductivity (EC) of 1.1 dS·m−1 (control) or saline solution at an EC of 5.0 dS·m−1 (EC 5) or 10.0 dS·m−1 (EC 10). At harvest, YH × Hamburg and YW × Nigra in EC 5 and EC 10 still exhibited good quality with average visual scores greater than 4.1 (0 = dead; 5 = excellent). For YW × Oakhill, moderate foliar salt damage was observed with an average visual score of 2.9 in EC 5 and 2.2 in EC 10. Compared with control, the shoot dry weight of YH × Hamburg, YW × Nigra, and YW × Oakhill in EC 5 reduced by 35%, 35%, and 55%, respectively, whereas that in EC 10 decreased by 58%, 58%, and 67%, respectively. Elevated salinity also decreased plant height, leaf area, and leaf greenness [Soil Plant Analysis Development (SPAD) readings]; chlorophyll fluorescence (Fv/Fm); performance index (PI); and net photosynthetic rate (Pn). All these responses might result from excess accumulation of sodium (Na+) and chloride (Cl−) ions in hydrangea leaves. In this study, compared with control, leaf Na+ concentration of YH × Hamburg, YW × Nigra, and YW × Oakhill increased 11, 36, and 14 times, respectively, in EC 5, and 31, 53, and 18 times, respectively, in EC 10. Compared with control, leaf Cl− concentration increased 4, 9, and 7 times in EC 5, and 10, 11, and 8 times in EC 10 for YH × Hamburg, YW × Nigra, and YW × Oakhill, respectively. Leaf nitrogen (N), phosphorous (P), potassium (K+), and iron (Fe3+) concentrations decreased at elevated salinity levels but did not cause any nutrient deficiency. In summary, the three Dichroa ×hydrangea hybrids exhibited different salinity tolerance: YH × Hamburg and YW × Nigra were more tolerant than YW × Oakhill. Salt-tolerant hydrangea hybrids should be chosen for landscape use if soil and/or irrigation water are salty.